Strategies for school buildings refurbishment in Portuguese climate - Barbosa, Francisca Cavaleiro (2020)
Portuguese school buildings are generally characterized by an in-service thermal discomfort, due to the poor envelope thermal properties and the lack of resources for paying energy consumption. Most Portuguese schools are free-running buildings with a natural ventilation strategy. Hundreds of high and basic schools have not been refurbished and still have problems or anomalies and inadequate in-service conditions and need to be rehabilitated in the near future. There will be, therefore, an opportunity to apply the acquired knowledge of comfort, habits, energy consumption and costs that have been studied since the last refurbishments (2008). This work studies the Portuguese Brandão schools model (from the ’70s), including about 100 non-refurbished basic schools. A prototype classroom was prepared in a Brandão school, in Porto. The in situ experimental campaign consisted of temperature, relative humidity, CO2 concentration and energy consumption measurements. The main tasks of this work are: (1) the validation of an advanced hygrothermal model with experimental measurements before and after the prototype refurbishment; (2) development of a sensitivity study in order to choose the best refurbishment and heating strategies for these buildings, regarding their typology, the local climate features and the actual capacity to support the operating costs; (3) assessment of the roof insulation thickness in Brandão schools; (4) quantification of discomfort indicators.